Pengaruh Investasi Asing dan Upah Minimum Provinsi terhadap Kesempatan Kerja Industri Besar Di Indonesia: dengan variabel moderasi pertumbuhan ekonomi - Yuni Hanita; Sri Ulfa Sentosa (Universitas Negeri Padang, 2022)
The studies aims to examine the effect of foreign investment and the Provincial Minimum Wage on job opportunities in large industries in Indonesia with the moderating variable of economic growth. The type of research used is descriptive and associative research. The data used in this study is panel data from 33 provinces in Indonesia in 2014-2018. The variables used in this study are foreign investment, UMP, economic growth and employment opportunities. This study uses moderated regression analysis, classical assumption test and hypothesis testing. The results Of the study show: (1) foreign investment has a significant positive relationship to large industrial employment opportunities in Indonesia, (2 provincial minimum wages are significant and have a negative relationship to large industrial employment opportunities in Indonesia, (3) economic growth is not significant and has a negative relationship positive on employment opportunities for large industries in Indonesia, (4) economic growth is able to moderate foreign investment on employment opportunities for large industries in Indonesia, (5) economic growth is not able to moderate the influence of the provincial minimum wage on employment opportunities for large industries in Indonesia. For the future to researchers so on to add other variables outside of this research variable to find out other variables that affect the employment opportunities of large industries in Indonesia.